2022
DOI: 10.1002/ase.2217
|View full text |Cite
|
Sign up to set email alerts
|

Faculty retirements will likely exacerbate the anatomy educator shortage

Abstract: Medical education has reported a shortage of anatomy educators since the 1960s. While the faculty pipeline has recently been explored, insights into retirement intentions, a key driver of faculty turnover, have yet to be investigated. With the mean age of anatomists rising, knowledge of retirement intentions among current educators is essential to understanding the anatomy educator shortage. This study explored the retirement intentions of current anatomy educators and their likely effects on the workforce. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…In 2002, 41 years later, a national survey found that more than 80% of chairpersons anticipated difficulty in recruiting and hiring qualified anatomy educators (Holden, 2003). More recent reports, as of 2020, have explored the anatomy educator shortage from a variety of viewpoints including chairperson perspectives (Wilson et al, 2020), American Association for Anatomy (AAA) annual job posting outcomes (Wilson et al, 2020), National Science Foundation (NSF) outcomes from the Survey of Earned Doctorates (Wilson et al, 2021), and AAA membership retirement intentions (Edwards et al, 2022). Collectively, this information points to a continued and widening shortage of anatomy educators.…”
Section: History Of the Anatomy Educator Shortagementioning
confidence: 99%
See 1 more Smart Citation
“…In 2002, 41 years later, a national survey found that more than 80% of chairpersons anticipated difficulty in recruiting and hiring qualified anatomy educators (Holden, 2003). More recent reports, as of 2020, have explored the anatomy educator shortage from a variety of viewpoints including chairperson perspectives (Wilson et al, 2020), American Association for Anatomy (AAA) annual job posting outcomes (Wilson et al, 2020), National Science Foundation (NSF) outcomes from the Survey of Earned Doctorates (Wilson et al, 2021), and AAA membership retirement intentions (Edwards et al, 2022). Collectively, this information points to a continued and widening shortage of anatomy educators.…”
Section: History Of the Anatomy Educator Shortagementioning
confidence: 99%
“…Duplicate postings and positions for postdoctoral trainees, chairpersons, administrators, basic science researchers, clinical positions, or adjunct/part‐time faculty were excluded from the analysis. Fewer job postings in 2020 were likely a direct consequence of the COVID‐19 pandemic (Edwards et al, 2022). The proportion of schools that have posted job openings consecutively from one year to the next has remained relatively constant over time and has not exceeded 25% of the total number of postings (Figure 2).…”
Section: Update: Job Postings Continue To Risementioning
confidence: 99%
“…At a time when anatomy faculty retirements are forecasted to outpace the inflowing anatomy workforce pipeline (Wilson et al, 2021; Edwards et al, 2022), it is critical for department leaders and anatomy educators to evaluate how well departmental expectations and practices align with national norms; as significant malalignment could lead to higher faculty turnover, dissatisfaction, and/or burnout. Department leaders are best positioned to advocate for workplace improvements and promote positive change when they leverage the known ties between the quality of departmental governance and faculty's overall satisfaction (Dandar & Bunton, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, this work explores: (i) faculty time allocations, (ii) faculty labor distribution models, (iii) anatomy teaching services offered, and (iv) faculty compensation practices pertaining to merit/cost-ofliving increases and bonuses. In light of newer reports emphasizing the growing anatomy educator shortage (Wilson et al, 2020(Wilson et al, , 2021Edwards et al, 2022), it is timely for anatomy-related departments across the U.S. and internationally to carefully evaluate their workload practices and competitiveness for attracting well-qualified candidates to open faculty positions. If leaders are better informed regarding national departmental trends, over time, they may be able to reduce their direct and hidden costs associated with time intensive operations, such as high faculty turnover and recruitment (Schloss et al, 2009).…”
Section: Study Purposementioning
confidence: 99%
“…Like previous work (Wilson et al, 2021;Garnett et al, 2023), information uncovered during this study indicated that approximately 22 students graduate each year from anatomy doctoral programs. Previous research has identified the need for more anatomy educators (Couzin-Frankel, n.d.;Eldred & Eldred, 1961;Bird, 1979;Heylings, 2002;Holden, 2003;McCuskey et al, 2005;Memon, 2009;Schaefer et al, 2019;Wilson et al, 2020Wilson et al, , 2021Edwards et al, 2023;Garnett et al, 2023) and has given recent projections for future anatomy faculty retirements (Edwards et al, 2023). In brief, the anatomy educator shortage is expected to continue, if not worsen (Edwards et al, 2023;Garnett et al, 2023).…”
Section: Anatomy Educator Shortagementioning
confidence: 99%